Dioxin and Polychlorinated Biphenyl Concentrations in Mother's Serum and the Timing of Pubertal Onset in Sons - Humblet, Olivier (2011)
BACKGROUND: Animal studies have demonstrated that timing of pubertal onset can be altered by prenatal exposure to dioxins or polychlorinated biphenyls (PCBs), but studies of human populations have been quite limited. METHODS: We assessed the association between maternal serum concentrations of dioxins and PCBs and the sons’ age of pubertal onset in a prospective cohort of 489 mother–son pairs from Chapaevsk, Russia, a town contaminated with these chemicals during past industrial activity. The boys were recruited at ages 8 to 9 years, and 4 years of annual follow-up data were included in the analysis. Serum samples were collected at enrollment from both mothers and sons for measurement of dioxin and PCB concentrations using high-resolution mass spectrometry. The sons’ pubertal onset—defined as pubertal stage 2 or higher for genitalia (G) or pubic hair (P), or testicular volume >3 mL—was assessed annually by the same physician. RESULTS: In multivariate Cox models, elevated maternal serum PCBs were associated with earlier pubertal onset defined by stage G2 or higher (4th quartile hazard ratio = 1.7 [95% confidence interval = 1.1– 2.5]), but not for stage P2 or higher or for testicular volume >3 mL. Maternal serum concentrations of dioxin toxic equivalents were not consistently associated with the sons’ pubertal onset, although a dose-related delay in pubertal onset (only for G2 or higher) was seen among boys who breast-fed for 6 months or more. CONCLUSIONS: Maternal PCB serum concentrations measured 8 or 9 years after sons’ births—which may reflect sons’ prenatal and early-life exposures—were associated with acceleration in some, but not all, measures of pubertal onset.